Measuring Line Length - Ahmed Saad Goher; Paolo Vaccarone (Arab Journal of Forensic Sciences & Forensic Medicine)
The scientific methodology for forensic examination of handwriting is based on studying the individual handwriting features and characteristics that distinguish its writer from others. The general qualities and the more detailed ones, some of which are "static" and refer to pictorical elements, while others refer to the pen's "dynamic" movement are investigated. Forensic handwriting experts during their daily activities are asked to analyse various features, many of which are suggested by the most prominent authors (connections, dimensions, proportions, shape, inclination, line quality, etc.), some of which are measurable, while others can only be inferred. However, the recent emergence of digitally captured signature (DCS) technology in the forensic field, has enabled the expert to analyse and evaluate new aspects, such as the length of the line. In the present study, an attempt has been made to study the line length and its possible uses in forensics handwriting examination processes. The authors, with different backgrounds and with different writing styles (Latin alphabet - Arabic alphabet), have tried to go further than the so far known study of handwriting for forensic purposes, studying and comparing the genuine lengths of the signature line and those that are forged (simulated).